Treatment of mycotic rhinitis caused by aspergillus fumigatus in a quarter horse mare using topical clotrimazole and oral potassium iodide - de Moura Alonso, Juliana; Watanabe, Marcos Jun [UNESP]; de Moraes Gimenes Bosco, Sandra; Apolonio, Emanuel Vitor Pereira [UNESP]; de Vasconcelos, Artur Bibiano [UNESP]; do Prado, Ana Carolina [UNESP]; Alves, Ana Liz Garcia [UNESP]; Rodrigues, Celso Antonio [UNESP]; Hussni, Carlos Alberto [UNESP] (Springer Nature, 2025)
Fungal rhinitis in horses is rare, although severe, due to the progressive nasal obstruction. Aspergillus is one of the fungi most often involved in these cases. A 7-year-old Quarter Horse mare weighing 325 kg was admitted with a history of recurrent nasal discharge and bleeding, foul smell, reluctance to exercise, and abortion. Laboratory and imaging examinations revealed eosinophilia, scarring and erosion areas in the nasal mucosa, purulent and bloody secretions, and remarkable yellowish plaques. Histopathological examination revealed fungal rhinitis and bacterial culture revealed the presence of β-hemolytic Streptococcus and Staphylococcus sp. Fungal culture and molecular diagnosis confirmed Aspergillus fumigatus as the etiological agent. A tracheostomy was necessary due to the patient’s dyspnea. For the treatment, topical application of clotrimazole ointment was carried out in the rostral portion of the nasal cavity once a day and in the caudal portion of the nasal cavity, endoscopic guided every 48 h. In the fifth endoscopy-guided application, a significant improvement was noticed; however, the animal exhibited a hypersensitivity reaction, and the treatment was discontinued. Thus, potassium iodide therapy was initiated (67 mg/kg, PO, SID, 14 days). The patient demonstrated favorable clinical improvement, achieved resolution of the fungal infection, and was discharged after 25 days of hospitalization. Topical clotrimazole demonstrated a probable efficacy as a standalone treatment, although its use had to be prematurely discontinued due to the emergence of a hypersensitivity reaction. The combination of clotrimazole and potassium iodide effectively treated fungal rhinitis in a shorter time than previously reported. This report provides useful guidance for other cases of fungal rhinitis, although further studies are needed.
Keywords: Antifungal; Aspergillosis; Aspergillus Fumigatus; Mycosis; Nasal cavity